Analysis of Adverse Reactions in Elderly Patients Based on Quantitative Methods of Signal Detection - K. E. Zalolochina; E. A. Ushkalova; A. S. Kazakov; S. K. Zyryanov; V. A. Polivanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2021)
A well-known problem in pharmacotherapy is an increased risk of adverse drug reactions (ADRs) in older as compared to younger patients. The Russian pharmacovigilance database includes a significant number of spontaneous reports of suspected ADRs in patients aged 65 and older. An increase in ADRs reporting makes it difficult to identify potential safety signals based on qualitative approaches only, which necessitates the use of statistical methods for signal detection based on disproportionality.The aim of the study was to assess the applicability of quantitative methods for signal detection and analysis of ADR risks in the elderly using the Russian spontaneous report database.Materials and methods: the study covered the reports on patients 65 years of age and older, which were submitted to the spontaneous report database from January 2008 until June 2018. The procedure recommended by the European Medicines Agency was used to identify potential statistical safety signals which were determined based on the following criteria: Reporting Odds Ratio, ROR-lower bound of the 95% confidence interval >1, number of cases ≥2; Proportional Reporting Ratio, PRR ≥ 2, Chi-square value χ2 ≥ 4, number of cases ≥3, lower bound of the 95% confidence interval >1, number of cases ≥3.Results: 2231 potential statistical signals were identified. Of these, the vast majority of combinations of suspected drugs and ADRs were associated with known drug risks, and were not new safety signals for these drugs. The largest proportion of statistical signals was attributed to the following pharmacological groups: antiplatelet agents, cephalosporins, non-steroidal anti-inflammatory drugs, fluoroquinolones, angiotensin-converting enzyme inhibitors, metabolic agents, and indirect anticoagulants.Conclusion: the results obtained indicate the applicability and effectiveness of statistical methods based on disproportionality of reporting for the analysis of the Russian spontaneous report database in order to identify potential drug safety issues.